1977
DOI: 10.1159/000459712
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Malformations in Squirrel Monkey (Saimiri sciureus) Fetuses with Emphasis on Cleft Lip and Palate

Abstract: Gross examination of a group of surviving and nonsurviving squirrel monkeys has revealed a high incidence of cleft lip and cleft primary palate defects with an associated anophthalmia. These defects, as well as single incidences of diaphragmatic aplasia, scoliosis, internal hydrocephalus, and funnel chest, are noted or described and discussed with reference to sex and parentage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…A rather higher frequency of congenital anomalies was detected in a squirrel monkey colony (Stills and Bullock, 1981), which included a full-term male stillborn with a typical left diaphragmatic hernia. Likewise, Baker et al (1977) found a similar defect in a stillborn female and refer to some consanguinity existing in their colony. The first indication of possible inheritance of diaphragmatic hernia came when Bush et al (1980) found this defect in 11 of 130 golden lion tamarins.…”
Section: Genetic Basis Of Congenital Anomaliesmentioning
confidence: 69%
“…A rather higher frequency of congenital anomalies was detected in a squirrel monkey colony (Stills and Bullock, 1981), which included a full-term male stillborn with a typical left diaphragmatic hernia. Likewise, Baker et al (1977) found a similar defect in a stillborn female and refer to some consanguinity existing in their colony. The first indication of possible inheritance of diaphragmatic hernia came when Bush et al (1980) found this defect in 11 of 130 golden lion tamarins.…”
Section: Genetic Basis Of Congenital Anomaliesmentioning
confidence: 69%
“…Gross examination of the associated fetuses revealed two with unclassified facial dysmorphia and two additional fetuses with oral-facial clefts, i.e., bilateral cleft lip and primary palate and left anophthalmia in one, and a bilateral cleft lip and unilateral cleft primary palate in the other [Baker et al, 1973]. In all four defective fetuses, the cord carried four vessels.…”
Section: Discussionmentioning
confidence: 98%
“…Studies examining the relationship between agricultural work and exposure to pesticides in mothers and congenital anomalies suggest that some agrochemicals disrupt the metabolic pathways that play a role in the development of cleft lip (García et al, 1999; Wyszynski and Beaty, 1996). In nonhuman primates, a high frequency of orofacial clefts has been reported in captive Saimiri sciurius related to consanguineous mating (Hoopes and Jerome 1987; Baker et al, 1977). Genetic, environmental, and nutritional factors require further study to explain the etiology of the anomalies that we have reported in chimpanzees here.…”
Section: Discussionmentioning
confidence: 99%